Profit Maximization for Small Medium-Sized Import Vehicle Company Using Linear Programming Approach - Osman, Nurathirah Camelia; Azila Md Sudin, (Enhanced Knowledge in Sciences and Technology, 2024)
In the highly competitive automotive industry, maximizing profit while balancing costs and revenues, poses a significant challenge. This study explores the use of linear programming to enhance profit optimization strategies for small and medium-sized import vehicle company. Through the development of a mathematical model, the aim is to maximize profit by determining the most efficient number of vehicle import services to accept. The problem is solved using the simplex method's linear programming approach, and this methodology is implemented efficiently through Excel Solver. Focusing on service provision rather than vehicle ownership, the research formulates constraints related to customer demand, time constraints, workforce limitations, and financial considerations. The results are obtained through the utilization of the linear programming solution and its subsequent sensitivity analysis. Numerous companies have used the linear programming approach to determine the most profitable outcomes, leading to the selection of SNK Cargo Company as the case of study for this profit maximization investigation. According to the results, the potential maximum profit the company could achieve amounts to RM56,000.00. This study will expose the organization to the linear programming method for strategic decision-making, specifically focusing on maximizing profits for import and export companies, particularly within the context of Malaysia.